Utilization of Artificial Intelligence in Supporting Learning Content Creativity for Javanese Language Teachers: a Systematic Literature Review - Cantika, Varary Mechwafanitiara; Munir, Munir (Lembaga Pendidikan Hikmatun Najah Blora, 2024)
The development of artificial intelligence (AI) technology opens up great opportunities to increase the creativity of learning content, including in Javanese language learning. This study aims to explore how AI can support teachers in creating creative and interesting Javanese language learning materials for students. This study adopts a qualitative approach with the Systematic Literature Review (SLR) method using secondary data from various scientific articles. Data sources were obtained from Google Scholar, accredited national journals, and reputable international journals. Data collection was carried out through documentation techniques, with strict selection criteria based on the 2022-2024 publication range, publisher reputation, and relevance to the research topic. Data were analyzed through a process of summarizing, synthesizing, and comparing key findings from various literatures, as well as critical evaluation of the strengths and weaknesses of each study. The results of the study show that AI, through generative tools such as ChatGPT, DALL·E, Gamma, and so on, enables Javanese language teachers to create varied, interactive, and adaptive materials to students' needs. This technology not only enriches the learning process but also plays an important role in preserving the Javanese language and culture through more contextual and interesting learning methods.